THE EFFECT OF SOCIAL MEDIA TIKTOK SHOP ON IMPULSE PURCHASES MEDIATED BY EMOTIONAL RESPONSE IN GENERATION Z IN PALU CITY - Ramadhani, Jihan; Parani, Syamsul Bahri Dg.; Santi, Ira Nuriya (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2024)
This study aims to determine the effect of TikTok Shop on impulse purchases mediated by emotional responses. This type of research is quantitative research which is one type of research whose specifications are systematic, planned and clearly structured from the beginning to the creation of its research design. The population in this study is an element of Generation Z in Palu City whose number is unknown. In this study using purposive sampling technique, which is a sampling technique with certain considerations so that the number of samples obtained was 90 people who were Generation Z in Palu City. Hypothesis testing was carried out using the Structural Equation Model (SEM) method using Partial Least Square (PLS) software, namely SmartPLS 3.0 software. So that the results showed that the TikTok Shop Social Media Variable had a positive and significant effect on Generation Z Impulse Purchases in Palu City. The TikTok Shop Social Media variable has a positive and significant effect on the Emotional Response of Generation Z in Palu City. The Emotional Response variable has a positive and significant effect on Generation Z Impulse Purchases in Palu City. The Emotional Response variable mediates the effect of Social Media TikTok Shop on Generation Z Impulse Purchases in Palu City.